The World of Applied Electromagnetics In Appreciation of Magdy Fahmy Iskander (Springer International Publishing, 2018)
This book commemorates four decades of research by Professor Magdy F. Iskander (Life Fellow IEEE) on materials and devices for the radiation, propagation, scattering, and applications of electromagnetic waves, chiefly in the MHz-THz frequency range as well on electromagnetics education. This synopsis of applied electromagnetics, stemming from the life and times of just one person, is meant to inspire junior researchers and reinvigorate mid-level researchers in the electromagnetics community. The authors of this book are internationally known researchers, including 14 IEEE fellows, who highlight interesting research and new directions in theoretical, experimental, and applied electromagnetics. Provides a single-source reference to many of the most significant developments of the past four decades in theoretical and applied electromagnetics; Offers current research trends in each sub-discipline discussed, the state of the art, the chief tools needed in that sub-discipline, and the vision of a research leader for that sub-discipline; Includes content of particular interest in Antennas and Propagation, as well as Microwave Theory and Techniques.